Opting in with the joneses: What affects the timing of municipal adoption of a local-option meals tax? - Bo Zhao (Federal Reserve Bank of Boston, 2021)
States use local-option taxes to promote local revenue diversification and improve local fiscal health. However, many sub-state governments wait a long time before adopting local-option taxes or do not adopt them at all, which seems puzzling or even irrational upon first glance. This paper uses the localoption meals tax in Massachusetts as a case study to examine the factors that affect the timing of local adoptions. It finds significant positive results for adoption by neighboring municipalities, which are robust to a variety of specifications, neighbor definitions, and weighting matrices. The adoption hazard also increases if a municipality faces greater fiscal stress, such as being more constrained by a property tax limitation or receiving a larger cut in state aid. In addition, the form of local government, size of the meals tax base, and ability to export the tax to non-residents are important factors.
Keywords: C41; H71; H73; H77; R50; 330; local-option tax; yardstick competition; policy diffusion; fiscal stress; hazard model